Long noncoding RNA TCL6 binds to miR‐106a‐5p to regulate hepatocellular carcinoma cells through PI3K/AKT signaling pathway. Issue 9 (5th February 2020) - Luo, Li‐Hua; Jin, Min; Wang, Lan‐Qing; Xu, Guo‐Jie; Lin, Zhen‐Yu; Yu, Dan‐Dan; Yang, Sheng‐Li; Ran, Rui‐Zhi; Wu, Gang; Zhang, Tao
Abstract: Long noncoding RNAs (lncRNAs) have been reported to dysregulate and involve in the pathology of hepatocellular carcinoma (HCC). Nonetheless, the functional role of lncRNA T cell leukemia/lymphoma 6 (TCL6) and its underlying mechanism in HCC remain unclear. Herein, we analyzed the expression of TCL6 and elucidated its mechanistic involvement in HCC. Bioinformatics analyses indicated TCL6 was evidently downregulated in HCC tissues compared with normal controls. TCL6 was downregulated while microRNA‐106a‐5p (miR‐106a‐5p) was upregulated in HCC cell lines. Moreover, knockdown or overexpression of TCL6 significantly raised or diminished the expression level of miR‐106a‐5p in HCC cells, similar to the effect of miR‐106a‐5p on TCL6 expression. Functionally, TCL6 inhibited the proliferative, migratory, and invasive potentials of HCC cells as analyzed by cell counting kit‐8, scratch wound healing, and transwell assays, respectively. Conversely, miR‐106a‐5p exerted an opposite effect on the proliferative, migratory, and invasive potentials of HCC. RNA immune precipitation and luciferase reporter assays revealed TCL6 directly bound to miR‐106a‐5p and luciferase reporter assay verified phosphatase and tensin homolog (PTEN) was a target gene of miR‐106a‐5p. Mechanistically, TCL6 knockdown evidently reduced PTEN expression at both messenger RNA and protein levels, and miR‐106a‐5p inhibitor partially rescued this reduction effect in HCC cells. Additionally, western blot assays demonstrated miR‐106a‐5p downregulation or TCL6 overexpression promoted the protein level of PTEN, and suppressed the phosphorylation level of AKT, the protein level of phosphatidylinositol 3‐kinase (PI3K). Collectively, these results revealed TCL6 as a tumor‐suppressive lncRNA regulates PI3K/AKT signaling pathway via directly binding to miR‐106a‐5p in HCC. This mechanism provides a theoretical basis for HCC pathogenesis and a potential therapeutic strategy for HCC treatment. Abstract : Long noncoding RNA T cell leukemia/lymphoma 6 (TCL6) was found to directly bind to microRNA‐106a‐5p (miR‐106a‐5p) to suppress the proliferation, migration, and invasion via phosphatidylinositol 3‐kinase/AKT signaling pathway in hepatocellular carcinoma (HCC). This work not only provides a theoretical basis for a better understanding of the mechanism of TCL6 in HCC but also indicated that TCL6 or miR‐106a might be considered as a biomarker in HCC.